Results of Survey and Evaluation of Invasive Plants in Ba Vi National Park, Vietnam - Tai, Vu Anh; Thi Bich Hong, Ngo; Thi Thuy Van, Tran; Thi Kim Thoa, Le (VNU Journal of Science: Earth and Environmental Sciences, 2023)
The biodiversity of Ba Vi National Park has been faced with some passive impacts, one of them is alien species, that habitats for the native species is narrowed by increasing of invasive population expanding, it is necessary to conducted a research on the impacts of the invasive plants there and then giving the basis for better management of the national park. After field surveys in recently years (2018-2022), 47 alliance species recorded at the National Park were evaluated according to guidance and data provided by Invasive Species Specialist Group (ISSG) and Centre for Agriculture and Biosciences International (CABI) developed Invasive Species Compendium (ISC) and also Circular 35/2018/TT-BTNMT. Result showed that 29 species were invaders and especially 11 species of them are detailly evaluated in 10 habitats.  2 species as Mexican sunflower ( Tithonia diversifolia ) and Lantana ( Lantana camara ) are evaluated as High risk for both areas while 3 other ones are evaluated as High risk for buffer zone only, including Giant sensitive tree), Leucaena ( Leucaena leucocephala ) and Giant sensitive plant ( Mimosa diplotricha ). The other ones have been evaluated as Medium risk (at buffer zone) to Low risk (at core area) are Blackjack ( Bidens pilosa ), Siam weed ( Chromolaena odorata ), Bay Biscayne creeping-oxeye ( Sphagneticola trilobata ), Jamaica cherry ( Muntingia calabura ), Jamaica vervain ( Stachytarpheta jamaicensis ) and Coast morning glory ( Ipomoea cairica ). By this evaluation, Mexican sunflower ( Tithonia diversifolia ), Blackjack ( Bidens pilosa ), Jamaica cherry ( Muntingia calabura ), Jamaica vervain ( Stachytarpheta jamaicensis ) and Coast morning glory ( Ipomoea cairica ) are suggested to include to the list of invasive organisms of the nation. Besides that, it is necessary to strengthen control of Mexican sunflower ( Tithonia diversifolia ) inside the core area of the NP in particular and in Ba Vi district in general, especially at the tourist place where the festival of Mexican sunflower has been yearly organized.